2020
DOI: 10.4103/jfmpc.jfmpc_134_20
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of the core indicators on drinking water and sanitation from urban slums of Jammu: A cross-sectional study

Abstract: Introduction: Water, sanitation, and hygiene (WASH) play an important role in decreasing the morbidity and mortality associated with poor WASH practices. Poor knowledge and awareness lead to an increase in communicable diseases. Objective: To assess and report the core indicators on sanitation and drinking water from urban slums using standardized WHO and UNICEF questionnaires. Materials and Methodology: The present observational cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[ 20 ] A study by Sangra et al . [ 21 ] also suggested that water-borne infection or related diseases could easily be prevented if water is safely handled by following simple measures such as covering the water container using a lid and treating water before consumption with methods such as boiling, candle filtration, chlorination techniques, or fetching water using a long-handled ladle. However, it was observed that very less number of participants followed these habits in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] A study by Sangra et al . [ 21 ] also suggested that water-borne infection or related diseases could easily be prevented if water is safely handled by following simple measures such as covering the water container using a lid and treating water before consumption with methods such as boiling, candle filtration, chlorination techniques, or fetching water using a long-handled ladle. However, it was observed that very less number of participants followed these habits in this study.…”
Section: Discussionmentioning
confidence: 99%